Analisis Strategi Gender Terhadap Pendidikan Anak Keluarga Petani Jambu Di Demak - Risti Lia Sari; Wulan Budi Astuti; Asa Salma Fatimah (LP2M, 2024)
Women's issues are still an important thing to discuss, in addition to continuing to develop, also many women's problems are never exhausted by a time or era of their presence on the surface of the earth, this is very visible when talking about the low resources of women, the problem of violence against women that occurs a lot either in the public or other sectorsThis research is a type of field researchÂ with qualitative research methods. Field research is research carried out at the research location or in the field. This technique is carried out by means of observation and recording on the object of study. The focus of observation is carried out on three main components, namely space, actors and activities.Â which aims to determine perceptions in providing education and efforts of guava farmer families in educating their daughters and sons. The results of this study attempt to determine the perception of guava farmer families in educating their daughters and sons are by distinguishing behavioral factors, age factors, interest factors, physical activity factors, biological development factors, closeness factors to both parents, and favorite